Combination therapy of anabolic and nonbisphosphonates antiresorptive agents for the treatment of osteoporosis: A meta-analysis. Issue 52 (December 2017) - Lou, Shenghan; Wang, Lifan; Wang, Yiwen; Jiang, Yunduo; Liu, Jingwei; Wang, Yansong
Abstract: Background: According to the mechanisms of action, combination therapy of anabolic and antiresorptive agents may produce more effect for the treatment of osteoporosis. However, the combination therapy of anabolic agents and bisphosphonates reports no benefit and even reduced the anabolic effects of anabolic agents. This study aims to assess the effect of combination therapy of anabolic and nonbisphosphonates antiresorptive agents in adults with osteoporosis. Methods: Medline, EMBASE, and Cochrane Library were searched from January 1, 1980 to November 1, 2017 for randomized controlled trials (RCTs) of adults with osteoporosis treated in combination therapy of anabolic and nonbisphosphonates antiresorptive agents compared with monotherapy of either agent alone. The primary outcome was the incidence of fractures. The secondary outcomes were the bone mineral density (BMD) changes at lumbar spine and total hip. Continuous outcomes were expressed as standardized mean difference (SMD) and 95% confidence interval (CI), while dichotomous outcomes were expressed as risk ratio (RR) and 95% CI. The meta-analysis was performed using a random-effects model. I 2 statistic ( I 2  > 50% as a threshold indicates significant heterogeneity) was used to assess the heterogeneity. Results: A total of 10 trials with a total of 1042 patients were included. The pooled results showed that the combination therapy demonstrated a significant advantage over a monotherapy in the BMD improvement at the lumbar spine (SMD 1.18; 95% CI, 0.63 to 1.72; I 2  = 93%) and the total hip (SMD 0.89; 95% CI, 0.48 to 1.29; I 2  = 88%) and further reduce the fracture risk (RR, 0.45; 95%CI, 0.21 to 0.94; I 2  = 0%). Conclusions: Low-to-moderate-quality evidence shows that the combination therapy of anabolic and nonbisphosphonates antiresorptive agents is superior to monotherapy in improving the BMD and reducing the fracture risk. However, further high methodological quality studies are needed to determine the antifracture efficacy, cost-effectiveness and safety of this strategy of combination therapy. Abstract : Supplemental Digital Content is available in the text